2022
DOI: 10.1371/journal.pone.0254270
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of a generic genome-scale metabolic network for chicken: Investigating network connectivity and finding potential biomarkers

Abstract: Chicken is the first sequenced avian that has a crucial role in human life for its meat and egg production. Because of various metabolic disorders, study the metabolism of chicken cell is important. Herein, the first genome-scale metabolic model of a chicken cell named iES1300, consists of 2427 reactions, 2569 metabolites, and 1300 genes, was reconstructed manually based on KEGG, BiGG, CHEBI, UNIPROT, REACTOME, and MetaNetX databases. Interactions of metabolic genes for growth were examined for E. coli, S. cer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…In 2022, the first G. gallus GEM, iES1300, was developed and used to investigate how metabolic requirements changes with cell types. Salehabadi et al (2022) found that fat and cancerous chicken liver cells are metabolically similar. They explained that this was due to their similarities of flux through certain pathways, namely, fatty acid synthesis, glycerophospholipid, and sphingolipid metabolisms.…”
Section: Chicken (Gallus Gallus)mentioning
confidence: 99%
See 2 more Smart Citations
“…In 2022, the first G. gallus GEM, iES1300, was developed and used to investigate how metabolic requirements changes with cell types. Salehabadi et al (2022) found that fat and cancerous chicken liver cells are metabolically similar. They explained that this was due to their similarities of flux through certain pathways, namely, fatty acid synthesis, glycerophospholipid, and sphingolipid metabolisms.…”
Section: Chicken (Gallus Gallus)mentioning
confidence: 99%
“…Salehabadi et al. (2022) found that fat and cancerous chicken liver cells are metabolically similar. They explained that this was due to their similarities of flux through certain pathways, namely, fatty acid synthesis, glycerophospholipid, and sphingolipid metabolisms.…”
Section: Animals Of Interest To the Cultivated Meat Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Chicken ( G. gallus ) is the most domesticated species in the poultry industry, and it is also the first sequenced avian creature. The first comprehensive GEM for the chicken was published in 2022, which consists of 2427 reactions, 2569 metabolites, and 1300 genes and was reconstructed manually based on databases including KEGG, BiGG, CHEBI, UNIPROT, REACTOME, and MetaNetX using the bottom–up approach [49].…”
Section: Gem Reconstructionmentioning
confidence: 99%
“…Statistical significance of differential expression of TSS and CTSS peaks was calculated using the DeSeq2 tool. Genome-scale metabolic model reconstruction: We utilized the recently published generic genome-scale metabolic model for chicken [1]. Then we fine-tuned the model for chicken whole embryo knowledge and data based on the original transcriptomics data and BioUML platform [2].…”
mentioning
confidence: 99%